GE_GERICHTE C/8726/2017 vom 11. Januar 2018 - GE Cour de justice (2018)
PROTECTION DE L'ADULTE CURATELLE DE REPRÉSENTATION(ANCIEN ART. 392 CC) ; CURATELLE DE GESTION(ANCIEN ART. 393 CC) | CC.388; CC.389; CC.390